Evolving Digital Consumption Behavior of Generation Z Muslim Consumers in the Halal Cosmetics Market - Vita Briliana (Journal of Digital Marketing and Halal Industry, 2025)
The growing awareness of halal lifestyles has transformed halal cosmetics in Indonesia from a mere trend into a daily necessity. Despite increasing demand, limited studies have explored the behavioral drivers influencing Generation Z Muslim consumers' online purchasing decisions for halal cosmetic products. This study aims to identify and analyze the relationships among key antecedents—religious commitment, halal marketing, halal certification, and celebrity endorsement—and determine which factor most strongly influences purchasing behavior. Data were collected through a standardized questionnaire distributed to 280 female Generation Z Muslim respondents across Indonesia. The relationships and hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that religious commitment, halal marketing, and halal certification have a significant influence on online purchase decisions, while celebrity endorsement has a minimal impact. These findings highlight the growing perception of halal as both a religious obligation and a trusted quality assurance for beauty products. The study contributes to a deeper understanding of digital consumer behavior in the halal industry, providing practical insights for marketers and policymakers seeking to strengthen halal brand positioning.